Investigating cranial morphological variation of early human skeletal remains from Chile: A 3D geometric morphometric approach - Kuzminsky, Susan C.; Baez, Omar Reyes; Arriaza, Bernardo; Mendez, Cesar; Standen, Vivien G.; San Roman Bontes, Manuel Julio; Munoz, Ivan; Duran Herrera, Angel; Hubbe, Mark (My University, 2018)
Objectives: Archaeological and genetic research has demonstrated that the Pacific Coast was a key route in the early colonization of South America. Research examining South American skeletons > 8000 cal BP has revealed differences in cranial morphology between early and late Holocene populations, which may reflect distinct migration events and/or populations. However, genetic, cultural, and some skeletal data contradict this model. Given these discrepancies, this study examines similar to 9000 years of prehistory to test the hypothesis that Early skeletons have a distinct cranial morphology from later skeletons. Materials and Methods: Using 3D digital models, craniofacial landmarks, and geometric morphometric analyses, we compared Early Holocene crania (n=4) to later Chilean samples (n=90) frequently absent in continental assessments of craniofacial variation. PCA, Mahalanobis distances, posterior and typicality probabilities were used to examine variation. Results: Two of the earliest skeletons from northern Chile show clear affinities to individuals from later sites in the same region. However, the hypothesis cannot be rejected as one Early individual from northern Chile and one individual from inland Patagonia did not always show clear affinities to coastal populations. Discussion: Biological affinities among northern populations and other regions of Chile align with genetic and archaeological data, supporting cultural and biological continuity along the Pacific Coast. In Patagonia, archaeological data are in accordance with skeletal differences between the Early inland steppe individual and coastal populations. This study incorporates 3D methods and skeletal datasets not widely used in assessments of biological affinity, thus contributing to a critical body of research examining the ancient population history of western South America.
Keywords: ancient human migration; bioarchaeology; early american crania; south america